Cold Pressor Stress Cardiac Magnetic Resonance Myocardial Flow Reserve Is Not Useful for Detection of Coronary Endothelial Dysfunction in Women with Signs and Symptoms of Ischemia and No Obstructive CAD. - Sofy Landes (PLoS ONE, 2017)
BACKGROUND:Coronary endothelial function testing using acetylcholine is not routinely available, while non-pharmacological cold pressor testing (CPT) is considered an endothelial stressor. Noninvasive cardiac magnetic resonance imaging (CMRI) myocardial perfusion reserve index (MPRI) can detect coronary microvascular dysfunction (CMD). We evaluated if CPT stress CMRI MPRI could detect invasive coronary endothelial dysfunction. METHODS:Coronary reactivity testing was performed in 189 women with symptoms and signs of ischemic but no obstructive coronary artery disease as previously described plus CPT stress. Subjects also underwent pharmacologic and CPT stress during CMRI (1.5 T). Statistical analysis comparing CPT MPRI between groups was performed by Welch`s t-test and Mann-Whitney where appropriate. Anderson-Darling test and Levene test were considered to verify the normality and homogeneity of variances assumptions. Correlation analyses between CPT MPRI and both invasive and noninvasive measures of CMD were performed using Spearman correlation. RESULTS:While CPT MPRI correlated with pharmacological stress MPRI, it did not correlate with invasive measures of CMD including invasively measured responses to intracoronary (IC) adenosine, IC acetylcholine, CPT, or IC nitroglycerin. Additionally CPT MPRI was not significantly different between subjects with normal compared to abnormal pharm stress MPRI or normal compared to abnormal invasive CMD parameters. CONCLUSION:Despite correlation with pharmacological stress MPRI, non-invasive CPT MPRI does not appear to be useful for detecting CMD in symptomatic women.